2002
DOI: 10.1046/j.1365-2125.2002.01598.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between body composition parameters and fluorouracil pharmacokinetics

Abstract: Aims To verify whether fluorouracil (FU) clearance (CL) and volume of distribution (V ss ) are better correlated with specific body compartments, such as body cell mass (BCM), total body water (TBW) or fat free mass (FFM), rather than with body surface area (BSA) or total body weight (BW). Methods Thirty-four patients (13 females and 21 males) affected by colorectal cancer and receiving FU as adjuvant therapy entered the study. CL and V ss were determined after a 2 min i.v. injection of FU (425 mg m x2 ) and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
59
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 20 publications
2
59
0
1
Order By: Relevance
“…Capecitabine is a prodrug that is metabolized to 5-FU. Consistent with our findings, Gusella et al (6) reported that fat-free mass (LBM plus bone tissue) and total body water were better predictors of 5-FU pharmacokinetics (clearance and volume of distribution) than BSA or total body weight.…”
Section: Discussionsupporting
confidence: 81%
“…Capecitabine is a prodrug that is metabolized to 5-FU. Consistent with our findings, Gusella et al (6) reported that fat-free mass (LBM plus bone tissue) and total body water were better predictors of 5-FU pharmacokinetics (clearance and volume of distribution) than BSA or total body weight.…”
Section: Discussionsupporting
confidence: 81%
“…Gusella et al (9) reported that fat-free mass (LBM without i.m. fat and fat in cell membranes) and total body water (intracellular and extracellular water) were better predictors of 5-FU pharmacokinetics (clearance and volume of distribution) than BSA or total body weight.…”
Section: Discussionmentioning
confidence: 99%
“…The differences seen in toxicities between patients were attributable to varia- tion in LBM [20]. Lean body mass was a better predictor of 5 FU pharmacokinetics than were standard anthropometric measures [21].…”
Section: Discussionmentioning
confidence: 95%